Financial Globalization : The Impact on Trade, Policy, Labor, and Capital Flows. (International Monetary Fund, 2007)
Assiduously tracking the trends and consequences of globalization, the IMF's quarterly magazine Finance and Development has been a major forum for discussing-and dissecting-the policy options and challenges faced by governments in an era when many national decisions transcend borders. This valuable compilation of articles published over the past eight years focuses on financial globalization, including the policy implications of the huge growth in cross-border capital flows. Articles also look at the expansion of world trade, explore the impact of globalization on jobs, taxation, and the poor, and examine the digital divide between developed and some developing countries. An extraordinary summary that distills nearly a decade of accelerated change.